Extended follow‐up after wearable cardioverter‐defibrillator period: the PROLONG‐II study. (4th September 2021) - Mueller‐Leisse, Johanna; Brunn, Johanna; Zormpas, Christos; Hohmann, Stephan; Hillmann, Henrike Aenne Katrin; Eiringhaus, Jörg; Bauersachs, Johann; Veltmann, Christian; Duncker, David
Abstract: Aim: The wearable cardioverter‐defibrillator (WCD) is used for temporary protection from sudden cardiac death (SCD) in patients with newly diagnosed heart failure with reduced ejection fraction before considering an implantable cardioverter‐defibrillator (ICD). However, the prognostic significance of the WCD remains controversial due to conflicting evidence. The aim of the present study was to evaluate prognosis of patients receiving life‐saving WCD shocks. Methods and results: All patients receiving a WCD at Hannover Medical School for heart failure with reduced ejection fraction between 2012 and 2017 were included. Data were acquired at baseline, at 3 months and at last available follow‐up (FU). Three hundred and fifty‐three patients were included (69% male; age 56 ± 15 years; left ventricular ejection fraction 25 ± 8%). FU after the WCD was 2.8 ± 1.5 years with a maximum of 6.8 years. Daily WCD wear time was 22 ± 4 h. Fourteen patients (4%) received appropriate WCD shocks. Two patients (0.6%) died during the WCD period. Thirty patients (9%) died during extended FU. Mean estimated survival after the WCD was similar between patients with and without WCD shocks. Patients without an ICD recommendation after WCD prescription did not experience SCD during FU. Conclusions: Patients with WCD shocks showed a favourable survival. Patients without an ICD recommendation after WCD prescription had no SCD during FU. These findings support the practice of careful risk stratification before considering an ICD and the use of the WCD for temporary protection from SCD.